"For the Future, For the Unborn": Considerations of History and Historians for Art Educators, Generated From George Orwell's Novel 1984. (3rd April 2017) - Bolin, Paul E.
Abstract : Beyond the well-recognized theme "Big Brother" or "Big Brother is Watching You" rests another very important yet frequently overlooked subject of George Orwell's novel 1984 . This less acknowledged cornerstone notion of the book centers on the triad of history, historical memory, and the historian. To investigate these thoughts regarding Orwell's 1984 and history-related matters, this investigation identifies five essential ideas about history and historians that have emerged through my reading of the novel. These ideas include: (1) The Uncertainty of the Historian, (2) The Impulse of the Historian, (3) The Power of the Historian, (4) The Responsibility of the Historian, and (5) The Connectivity of the Historian. Each of these five ideas is discussed, utilizing quotes from the book and related examples identified about and from the art education historical record.